1982
DOI: 10.1007/bf00120977
|View full text |Cite
|
Sign up to set email alerts
|

A cybernetic model for curriculum development

Abstract: The task of the curriculum developer is to design instructional systems which will produce consistently high levels of learning despite wide variation in pupil characteristics. This can be viewed as a cybernetic question of regulating variety in a system to produce stable and high level output. Six cybernetic principles -goal orientation, limitation of input, monitoring, control decisions, restoration of equilibrium, and positive feedbackare described, and their application to curriculum discussed. It is concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(3 reference statements)
0
1
0
1
Order By: Relevance
“…Öz düzenleme bilimi olarak tanımlanan bu kavramın program araştırmalarında yer edinebileceği düşünülmektedir. Öz düzenleme ilkeleri, öğrenmeyi öğrenme gibi çalışma konuları sibernetiğin içinde yer almakla birlikte geribildirim gibi terimlerin de eğitim bilimlerinde kullanıldığı görülmektedir (Pratt, 1982). Bu nedenle sınırlı sayıda araştırmanın olduğu tespit edilen sibernetiğin salgın sürecinde, uzaktan eğitim ile öz düzenleme ve öğrenmeyi öğrenme becerilerinin sorgulandığı mevcut durumda program araştırmalarına farklı bir boyut getireceği öngörülmektedir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Öz düzenleme bilimi olarak tanımlanan bu kavramın program araştırmalarında yer edinebileceği düşünülmektedir. Öz düzenleme ilkeleri, öğrenmeyi öğrenme gibi çalışma konuları sibernetiğin içinde yer almakla birlikte geribildirim gibi terimlerin de eğitim bilimlerinde kullanıldığı görülmektedir (Pratt, 1982). Bu nedenle sınırlı sayıda araştırmanın olduğu tespit edilen sibernetiğin salgın sürecinde, uzaktan eğitim ile öz düzenleme ve öğrenmeyi öğrenme becerilerinin sorgulandığı mevcut durumda program araştırmalarına farklı bir boyut getireceği öngörülmektedir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…The multidisciplinary science of cybernetics has shown that feedback is essential to the health and growth of all open and dynamic systems, from organic life to organizations and interpersonal relations. 42 Humanistic educators have often charged educational evaluators with bias in their attention to assessing acquisition of information and in norm-referenced judgements that aim to separate students as much as possible. Contemporary approaches emphasize diagnostic evaluation, the assessment of learning in relation to goals rather than relative to other learners, and qualitative as well as quantitative judgements.…”
Section: Feedbackmentioning
confidence: 99%